AUDIT ON HYSTERECTOMIES DONE IN PUMHS TERTIARY CARE. - Raishem Ali Baloach1, Farida Wagan2, Uzma Aslam3, Asifa Abdul Jabbar4, Naila Yousif Memon5, Yasmeen Joyo6., (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
BACKGROUND: Trend of hysterectomy varies geographically butstill considered as one of most frequently performed surgical procedure worldwide. Uterus should never be assumed as vestigial viscera once desired fertility is obtained. Being a major surgery this is not without risk and in account of newer treatment options, indication must be justified. OBJECTIVE: To audit on indication, complication and justification of hysterectomies done in PUMHS tertiary care Centre. STUDY DESIGN: Observational study. SETTING: Department of Obstetrics and Gynecology Unit 1 People University of Medical and Health Science Shaheed Benazir Abad. DURATION OF STUDY: One year from 1st January 2019 to 31st December 2019. METHODOLOGY: This study is done on patients admitted for elective hysterectomies in one-year duration, in PUHMS Tertiary care setting. These studies include all women decided for hysterectomy for benign conditions except obstetrical hysterectomy. Variables like age, parity, inhabitance, marital status, clinical presentations, indications, type and route of procedure, complications, ovarian preservation and histopathologyfindings noted and surgery justified if histopathology seems significantly abnormal. Data entered and analyzed on SPSS version 20. RESULT: In 2019 total 127 hysterectomies done suggest 6.2% incidence, 19 patient lost from follow up while 106 cases included in study. Most common age was 41 to 51 years with mean 51 observed. Majorities were married, had more than 5 children and were resident of rural areas.Majority presents with POP (pelvic organ prolapse) and menstrual irregularities. Common complications were minor (fever and UTI). Surgery justified in 89.6% of cases. CONCLUSION: Women aged between 41 to51 years were mostly underwent surgery. Most frequent indication was POP, next common menstrual irregularities due to fibroid, adenomyosis and pelvic inflammatory diseases. Abdominal approach most of the time used, vaginal route for only POP indication. Common complication observed infective sequel. Though justified in 89.6% of the cases but being major surgery with associated risk alternative options must offered